Start-up nation Israel: transnational entrepreneurs, born globals and cross-border connections of the Israeli high-tech industry - Schäfer, Susann; Henn, Sebastian (Research handbook on transnational diaspora entrepreneurship, 2023)
In this chapter, we explore the emergence and development of Israel's high-tech industry, which is so exceptional that Israel is often referred to as a "start-up nation". Right from the beginning, the Israeli high-tech industry has been significantly shaped by transnational linkages: New Argonauts played an important role for the emergence of the industry in the late 1970s, transferring industry-specific knowledge and technology from overseas to Israel. Still today, many high-tech entrepreneurs rely on cross-border ties to North America and Europe, for example, to develop new solutions or access venture capital. This chapter provides an overview of the economic, demographic, and political background of Israel's success story, with a particular focus on transnational corporate linkages. In addition to the main features of the regional entrepreneurial ecosystem, we present the development of selected high-tech firms, focusing on their cross-border linkages and spatial organization.
Gesehen am 29.01.2025